2019
DOI: 10.1097/md.0000000000014401
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs2910164 polymorphism in MiR-146a gene with psoriasis susceptibility

Abstract: The rs2910164 single nucleotide polymorphism (SNP) in miR-146a has been implicated in the etiology of psoriasis in different relevant studies with contradictory conclusions and limited sample size. Therefore, the aim of this study was to undertake a systematic review and meta-analysis to estimate the association between rs2910164 SNP and psoriasis. We searched the databases of PubMed, EMBASE, Web of Science, WanFang, and Chinese National Knowledge Infrastructure (CNKI) to identify relevant literatures publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Of note, the previously performed bioinformatic analysis revealed that the G allele of this variant may enhance the stability of the pre-miRNA secondary structure, leading to a potential improvement of the miRNA maturation process and thus to an enhanced production of the resulting miRNAs [15]. This evidence is line with literature data showing an overexpression of MIR146A in Ps [22,28]. However, miR-146a has also been regarded as a negative regulator of inflammation, because it is able to target Interleukin 1 Receptor-Associated Kinase 1 (IRAK1, Xq28) and TNF Receptor-Associated Factor 6 (TRAF6, 11p12), that are well-known pro-inflammatory factors [29,30].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Of note, the previously performed bioinformatic analysis revealed that the G allele of this variant may enhance the stability of the pre-miRNA secondary structure, leading to a potential improvement of the miRNA maturation process and thus to an enhanced production of the resulting miRNAs [15]. This evidence is line with literature data showing an overexpression of MIR146A in Ps [22,28]. However, miR-146a has also been regarded as a negative regulator of inflammation, because it is able to target Interleukin 1 Receptor-Associated Kinase 1 (IRAK1, Xq28) and TNF Receptor-Associated Factor 6 (TRAF6, 11p12), that are well-known pro-inflammatory factors [29,30].…”
Section: Discussionsupporting
confidence: 88%
“…This variant is located within the miRNA seed region of miR-146a, encoded by the MIR146A gene. Several studies tried to investigate the association of this SNP with Ps, but results were conflicting [22]. In the present study, the G allele confers a higher susceptibility to Ps and PsA.…”
Section: Discussionmentioning
confidence: 64%
“…Another study cited that susceptibility to pulmonary tuberculosis is not influenced by the MIR146A rs2910164 [ 48 ]. However, a meta-analysis approach on psoriasis case-control studies with rs2910164 revealed that the CC genotype is correlated with decreased risk of psoriasis [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…49,131 Polymorphisms that affect miR-146a expression was described as predisposing factors for many autoimmune diseases, including psoriasis. [141][142][143] MiRNAs are also involved in the regulation on other immune cell types. For example, Meng et al reported that miR-148a is a key modulator of moDC differentiation in psoriasis.…”
Section: Mir-155 Expression Is Increased Upon T-cell Activation and R...mentioning
confidence: 99%